Automated evaluation of setup errors in carbon ion therapy using PET: Feasibility study. Issue 12 (15th November 2013) - Kuess, Peter; Helmbrecht, Stephan; Fiedler, Fine; Birkfellner, Wolfgang; Enghardt, Wolfgang; Hopfgartner, Johannes; Georg, Dietmar
Abstract : Purpose: : To investigate the possibility of detecting patient mispositioning in carbon‐ion therapy with particle therapy positron emission tomography (PET) in an automated image registration based manner. Methods: : Tumors in the head and neck (H&N), pelvic, lung, and brain region were investigated. Biologically optimized carbon ion treatment plans were created with TRiP98. From these treatment plans, the reference β + ‐activity distributions were calculated using a Monte Carlo simulation. Setup errors were simulated by shifting or rotating the computed tomography (CT). The expected β + activity was calculated for each plan with shifts. Finally, the reference particle therapy PET images were compared to the "shifted" β + ‐activity distribution simulations using the Pearsonˈs correlation coefficient (PCC). To account for different PET monitoring options the inbeam PET was compared to three different inroom scenarios. Additionally, the dosimetric effects of the CT misalignments were investigated. Results: : The automated PCC detection of patient mispositioning was possible in the investigated indications for cranio‐caudal shifts of 4 mm and more, except for prostate tumors. In the rather homogeneous pelvic region, the generated β + ‐activity distribution of the reference and compared PET image were too much alike. Thus, setup errors in this region could not be detected. Regarding lung lesions the detection strongly depended on the exact tumor location: in the center of the lung tumor misalignments could be detected down to 2 mm shifts while resolving shifts of tumors close to the thoracic wall was more challenging. Rotational shifts in the H&N and lung region of +6° and more could be detected using inroom PET and partly using inbeam PET. Comparing inroom PET to inbeam PET no obvious trend was found. However, among the inroom scenarios a longer measurement time was found to be advantageous. Conclusions: : This study scopes the use of various particle therapy PET verification techniques in four indications. The automated detection of patientsˈ setup errors was investigated in a broad accumulation of data sets. The evaluation of introduced setup errors is performed automatically, which is of utmost importance to introduce highly required particle therapy monitoring devices into the clinical routine.